The Importance of Direct Progeny Measurements for Correct Estimation of Effective Dose Due to Radon and Thoron - Bineng, Guillaume Samuel; Saïdou,; Tokonami, Shinji; Hosoda, Masahiro; Tchuente Siaka, Yvette Flore; Issa, Hamadou; Suzuki, Takahito; Kudo, Hiromi; Bouba, Oumarou (Frontiers in Public Health, 2020)
Radon (Rn), thoron (Tn), and thoron progeny (TnP) were measured in seven inhabited areas of the uranium and thorium bearing region of Lolodorf, located in southwestern Cameroon. Then the equilibrium factor (FTn) between thoron and its progeny was determined in order to show the importance of direct progeny measurements for correct estimation of effective dose due to radon, thoron and their progenies. A total of 220 RADUET detectors were used to measure indoor radon and thoron and 130 TnP monitors for thoron progeny indoors. The arithmetic and geometric mean concentrations of Rn, Tn, and TnP were 103 and 89 Bq m−3, 173, and 118 Bq m−3, 10.7, and 7.4 Bq m−3, respectively. Total effective dose determined from radon, thoron, and their progenies was estimated at 4.2 ± 0.5 mSv y−1. Thoron equilibrium factor varied according to seasons, the type of dwelling, building materials and localities. Thoron (Tn and TnP) contribution to effective dose ranged between 3 and 80% with the average value of 53%. Total effective dose estimated from the world average equilibrium factor of 0.02 given by UNSCEAR was 2.7 ± 0.2 mSv y−1. The effective dose due to thoron varied greatly according to the different values taken by FTn and was different from that determined directly using TnP concentrations. Thus, effective dose due to thoron determined from the equilibrium factor is unreliable. Therefore, the risk of public exposure due to thoron (Tn and TnP) may therefore be higher than that of radon (Rn and RnP) in many parts of the world if FTn is no longer used in estimating total effective dose. This is not in contradiction with the UNSCEAR conclusions. It is therefore important to directly measure the radon and thoron progeny for a correct estimate of effective dose.